brModelo: An Initiative for Aiding Database Design - dos Santos Mello, Ronaldo; Cândido, Carlos Henrique; Bittencourt S. Neto, Milton (Journal of Information and Data Management, 2021)
The brModelo tool is a initiative of the UFSC Database Group. Its first version was developed in 2005, and its main purpose is to help teaching of relational database design. Compared to similar tools, its main differentials are the support to all steps of the classical database design methodology, user interaction during the logical design step, as well as the support to all extended Entity-Relationship concepts. With more than fifteen years of existence, the brModelo was very well-accepted by the brazilian Database community, which motivated the development and release of several versions of the tool. This article presents the history of brModelo, including its available versions and their functionalities. Additionally, we detail its functionalities and compare it with popular related tools.